1993
DOI: 10.3109/09638289309166002
|View full text |Cite
|
Sign up to set email alerts
|

The functional and psychological status of patients with amyotrophic lateral sclerosis: Some implications for rehabilitation

Abstract: Amyotrophic lateral sclerosis (ALS), known as motor neurone disease (MND) in Britain, poses special problems in rehabilitation by virtue of its nature, trajectory and the age of patients with the disease. Many practical difficulties of ALS are well known, but there has been little research on the psychological parameters of the disease. This study of 181 ALS patients, from a national register in England and Wales, indicates that, contrary to some previous research, psychological distress (measured by the Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…In agreement with the QoL literature discussed earlier, a number of studies demonstrate a lack of association between depression and physical measures of illness -illness severity, physical impairment, time since diagnosis, physical functioning, or illness progression [10,16,22,23]. In contradiction, two studies have found significant though weak associations between physical impairment and depression [12,18]; for instance one of these studies [12] determined that physical functioning accounted for just 3.2% of the total variance of psychological status.…”
Section: Depression Anxiety and Psychological Distressmentioning
confidence: 61%
See 3 more Smart Citations
“…In agreement with the QoL literature discussed earlier, a number of studies demonstrate a lack of association between depression and physical measures of illness -illness severity, physical impairment, time since diagnosis, physical functioning, or illness progression [10,16,22,23]. In contradiction, two studies have found significant though weak associations between physical impairment and depression [12,18]; for instance one of these studies [12] determined that physical functioning accounted for just 3.2% of the total variance of psychological status.…”
Section: Depression Anxiety and Psychological Distressmentioning
confidence: 61%
“…As can be seen in Table 1, the sample sizes range from 10 to 2018 and studies encompass patients at various stages of illness severity, progression and type of MND. Despite these inconsistencies, the larger studies with sample sizes over 100 show a prevalence of depression between 11% and 15% [3,9,12].…”
Section: Depression Anxiety and Psychological Distressmentioning
confidence: 75%
See 2 more Smart Citations
“…One study investigated whether general functional assessments were sensitive to disability in MND, 9 while another explored the contribution of functional impairment to patient psychological distress. 10 It remains unknown, however, how functional decline relates to the severity of MND. 11 It may be predicted that upper limb dysfunction is a major determinant of ADL given their dependence on hand function, but the contribution of behavioural changes in functional disability in MND is unknown.…”
Section: Introductionmentioning
confidence: 99%